3D mapping of the neutral X-ray absorption in the local interstellar medium: the Gaia and XMM-Newton synergy. Issue 3 (30th June 2018) - Gatuzz, Efraín; Kh., S Rezaei; Kallman, Timothy R; Kreikenbohm, Annika; Oertel, Mirjam; Wilms, J; García, Javier A
ABSTRACT: We present a three-dimensional map of the hydrogen density distribution in the Galactic interstellar medium. The hydrogen-equivalent column densities were obtained from the Exploring the X-ray Transient and variable Sky project (EXTraS ) which provides equivalent N H values from X-ray spectral fits of observations within the XMM-Newton Data Release. EXTraS include multiple fits for each source, allowing an accurate determination of the equivalent column densities, which depends on the continuum modelling of the spectra. A cross-correlation between the EXTraS catalogue and the first Gaia Data Release was performed in order to obtain accurate parallax and distance measurements. We use a Bayesian method explained in Rezaei Kh. et al. (2017 ) in order to predict the most probable distribution of the density at any arbitrary point, even for lines of sight along which there are no initial observation. The resulting map shows small-scale density structures which could not have been modelled by using analytic density profiles. In this paper, we present a proof of concept of the kind of science possible with the synergy of these catalogues. However, given the systematic uncertainties connected to the source identification and to the dependence of N H on the spectral model, the present maps should be considered qualitatively at this point.